2021
DOI: 10.1021/acs.jafc.0c07664
|View full text |Cite
|
Sign up to set email alerts
|

Type III Resistant Starch Prepared from Debranched Starch: Structural Changes under Simulated Saliva, Gastric, and Intestinal Conditions and the Impact on Short-Chain Fatty Acid Production

Abstract: Type III resistant starch (RS3) has high resistance to enzymatic digestibility and benefits colonic bacteria by producing short-chain fatty acids (SCFAs) via fermentation. Studies have delineated RS preparation and the description of RS fractions with different types of starch, but the digestion process has received little attention. The molecular and crystalline structure changes, thermal properties, and SCFA content of RS3 obtained from debranched starch were investigated in simulated salivary, gastric, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Several clinical trials showed that RS2 increased abundance of Bifidobacteria and increased production of SCFAs [59]. RS3 produced large amounts of butyric acid after fermentation in vitro [60]. A recent study in an in vitro fermentation system showed that RS5 was superior in the production of butyrate while RS3 produced more lactic acid [61].…”
Section: Resistant Starchesmentioning
confidence: 99%
“…Several clinical trials showed that RS2 increased abundance of Bifidobacteria and increased production of SCFAs [59]. RS3 produced large amounts of butyric acid after fermentation in vitro [60]. A recent study in an in vitro fermentation system showed that RS5 was superior in the production of butyrate while RS3 produced more lactic acid [61].…”
Section: Resistant Starchesmentioning
confidence: 99%
“…Previous studies have provided important insights into the role of starch structure in the fermentation process of resistant starch. For an in-depth investigation of this relationship, butyrylated starch digesta were isolated for further structural analyses and simulated fermentation. Observation of the morphological structure of butyrylated starch revealed a porous morphology with numerous tiny holes on the surface of digested B-WMS, suggesting a tendency to evolve into a honeycomb structure in the subsequent fermentation process.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was filtered through a 0.22 μm membrane filter, and it was analyzed at 30 °C and 0.4 mL/min flow rate. In addition, the RS3a and RS3b residue suspensions were measured directly through the membrane after heating and gelatinizing without debranching enzymatic hydrolysis, using high-performance anion-exchange chromatography with pulsed amperometric detection (HPAEC-PAD, ICS-5000+, Dionex, Sunnyvale, California) following the procedure described by Chang et al 5 Crystalline Structure. The crystal structures of starch samples were analyzed by X-ray diffraction (XRD).…”
Section: Structure and Thermal Property Determination Of The Rsmentioning
confidence: 99%
“…A previous investigation on the digestive process of recrystallized RS in simulated salivary, gastric, and intestinal digestion systems found that enzyme-resistant starch might be formed during RS3 digestion by the rearrangement of short amylose chains into enzyme-resistant structures with higher relative crystallinity. 5 However, the digestive process of recrystallized RS in vivo has rarely been studied. As the digestive tract environment is very complex, there are differences between in vitro modeling and in vivo results.…”
Section: ■ Introductionmentioning
confidence: 99%